The Influence of Supervisor, Teamwork, and Discipline on Employee Performance - Sembiring, Nia Mutiara; Syarifuddin, Syarifuddin (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
PT Dinamika Nuansa Absolute is a company engaged in the field of outsourcing, providing call center services. An organization greatly relies on human resources to achieve its goals. This necessitates the proper and effective management of human resources within the company or organization. Numerous factors can influence human resources, such as supervision, teamwork, discipline, and employee performance. The purpose of this research is to analyze the impact of Supervision, Teamwork, and Discipline on Employee Performance at PT Dinamika Nuansa Absolute. This research employs a quantitative approach with descriptive and causality research types. Non-probability sampling using the saturated sample method was conducted, resulting in 102 respondents from PT Dinamika Nuansa Absolute. Data analysis techniques include descriptive analysis and multiple linear regression analysis. The findings partially indicate that Supervision, Teamwork, and Discipline individually have a positive and significant influence on employee performance. Additionally, when considered together, Supervision, Teamwork, and Discipline collectively exert a significant influence on employee performance. The results suggest that the independent variables (Supervision, Teamwork, and Discipline) account for 45% of the variance in employee performance, with the remaining 55% influenced by unexamined factors.